Evaluasi Sistem Bantuan Stimulan Pembiayaan Perumahan Swadaya di Kabupaten Malang - Juniarko, Oky; Surjono, Surjono; Anwar, M. Ruslin (Jurnal Tata Kota dan Daerah, 2012)
House is one of the basic human need for survival. However, not all individuals have the same ability to comply housing needs. The aim of this study was to evaluate the mechanism of BSP2S system in Malang. The research method used are descriptive analysis method to describe the mechanism of the housing stimulant grants and Important Performance Analysis (IPA) to evaluate the performance of the housing stimulant finance program . The housing finance programs with a pure grant mechanism is an effort in complying the housing backlog besides mortgages mechanisms. Utilization of the housing stimulant grants through the home construction was able to reduce approximately 0.23% backlog (43 930 units) of housing need in 2011. Some things that need to be improved in housing finance programs are coordination aspect, the grants amount, improving the quality of human resources and the quality of infrastructure.Keywords: self-built housing, housing finance, backlog.